The Factors Affecting Vanilla Farm Productivity in Gianyar, Bali - Dewi, Ni Made Kisna; Marhaeni, A.A I N (Universitas Negeri Malang, 2018)
The main problem of vanilla farming is the lack productivity of vanilla farmers as indicated by the decreasing productivity every year. This research was conducted in Gianyar Regency, Bali, Indonesia. Data used in this research are primary data and secondary data. While the sample in this study is vanilla farmers, amounting to 160 people. This research used descriptive analysis and inferential statistics by using path analysis. The findings of this research are the average productivity level of vanilla farm in Gianyar Regency is good enough, it is very effected by the amount of capital, technology, training through entrepreneurial variable. Second, the calculation result shows technological and training variables have direct and significant effect to entrepreneurship, while capital variable indirectly effect entrepreneurship. Third, capital variables, technology, training and entrepreneurship have a direct and significant effect on productivity. Fourth, the results of indirect calculating indicates that the variable amount of capital, technology, and training on productivity has indirect affect through entrepreneurship variable.Keywords: Farming productivity; entrepreneurship; capitalJEL Codes: P24, Q12